2016
DOI: 10.1007/s11483-016-9442-7
|View full text |Cite
|
Sign up to set email alerts
|

Biological Effect and Inactivation Mechanism of Bacillus subtilis Exposed to Pulsed Magnetic Field: Morphology, Membrane Permeability and Intracellular Contents

Abstract: Biological effect and inactivation mechanism of Bacillus subtilis exposed to pulsed magnetic field (PMF) were investigated. Cell morphology, membrane permeability, release of intracellular proteins and damage of deoxyribonucleic acid (DNA) were monitored. The inactivation effect of PMF treatment on B. subtilis was enhanced with the increase in intensity and pulse number. Scanning electron microscopy (SEM) analysis showed that the PMF treated bacterial cells had rough surfaces and damaged cellular membranes. Fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The inactivation mechanisms of PMF on microorganism have also been elucidated and can be attributed to the disruption of the cell membrane and the leakage of the intracellular substance (Lin et al, 2019;Qian et al, 2016a). Moreover, PMF affected the proteome of bacterial, leading to the disorder of physiology function and energy metabolism (Qian et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inactivation mechanisms of PMF on microorganism have also been elucidated and can be attributed to the disruption of the cell membrane and the leakage of the intracellular substance (Lin et al, 2019;Qian et al, 2016a). Moreover, PMF affected the proteome of bacterial, leading to the disorder of physiology function and energy metabolism (Qian et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…The survival rate generally decreased with the increase of intensity and pulse number. It has been reported that the inactivation rate of microorganism treated by PMF depends on intensity and pulse number(Qian et al, 2016a). However, the population of mesophilic bacteria could not be completely inactivated, exhibiting the highest log reduction (0.61) at the intensity of 7 T with pulse number of 20.…”
mentioning
confidence: 99%
“…A classic indication of bacterial cytoplasmic membrane damage was determined by measuring the leakage of cytoplasmic contents (Qian et al ). The leakage of nucleic acid and protein‐related substances in E. coli O157:H7 was consistent with the membrane changes observed by SEM, where more pores formed on the membrane of OH‐treated E. coli O157:H7 cells than WB‐treated ones.…”
Section: Discussionmentioning
confidence: 99%
“…The equipment was warmed up for 10 min to ensure the stability of voltage and then required an interval of 2 min between each operation for cooling. Based on the previous studies, the samples were subjected to PMF treatment at the intensities of 1.0-3.5 T with the pulses of 10-35 Xu & Ma, 2010;He et al, 2014;Qian et al, 2016), at 30.0 AE 0.2°C and pH 7.4.…”
Section: Pmf Treatmentmentioning
confidence: 99%
“…Pulsed magnetic field (PMF) is such a nonthermal processing method that is able to affect bacterial behaviours and even inactive their activity using appropriate intensities and pulse numbers (Qian et al, 2016). In comparison with conventional thermal-and chemical-processing methods, PMF technology shows more advantages, such as saving process duration time, environment-friendly operations without extra destructions and no chemical residue as well.…”
Section: Introductionmentioning
confidence: 99%